Molecular beam epitaxy grown GeSn p-i-n photodetectors integrated on Si - Werner, J.; Oehme, Michael; Schirmer, A.; Kasper, E.; Schulze, J. (Thin Solid Films, 2012)
GeSn p-i-n photodetectors with a low Sn mole fraction made by molecular beam epitaxy on Si substrates show higher optical responsivities for wavelength λ > 1400 nm compared with p-i-n photodetectors made from pure Ge. The Sn incorporation in Ge is done by a low temperature growth step in order to minimize Sn segregation. The Sn incorporation and the alloy content are investigated by μ-Raman spectroscopy and calibrated Secondary Ion Mass Spectrometry. The photodetectors are manufactured with sharp doping transitions and are realized as double mesa structures with diameters from 1.5 μm up to 80 μm. The optical measurements are carried out with a broadband super continuum laser from λ = 1200 nm up to λ = 1700 nm. At a wavelength of λ = 1550 nm the optical responsivity of these vertical GeSn diodes is 0.1 A/W. In comparison with a pure Ge detector of the same geometrical dimensions the optical responsivity is increased by factor of three as a result of Sn caused band gap reduction. © 2011 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2021-06-29
Keywords: μ-Raman-spectroscopy; Ge photodetector; GeSn Epitaxie